Projeto didático de gênero: um estudo a partir do modelo didático de gênero e das capacidades de linguagem mobilizadas em trabalho com cartas de reclamação - Isabela Catarina Cunha Soares (2016)
The current work aims at analyzing possibilities of reading teaching and written production in Portuguese classes by means of text genres. Under the perspective of the genre didactic project (PDG), a methodological proposal relying on literacy projects (KLEIMAN, 2000; OLIVEIRA, 2008), and the didactic sequences (DOLZ; SCHNEUWLY, 2004), the workshops elaborated by three teachers from Universidade do Vale do Rio dos Sinos, who participated in the research project named "For a continued cooperative graduation for the development of the reading educational process and written text production in Elementary Teaching", have been reviewed. The research has been conducted by the case study method, using a qualitative approach, either during the analysis of workshops activities or in the treatment of data achieved via generated graphics. Language capacities (DOLZ E SCHNEUWLY, 2004; CRISTÓVÃO E STUTZ, 2011) taken as analysis categories and used in the activities created by the teachers have been checked. The extent to which the PDG workshops include the teachable elements described by the didactic model, a concept developed by Dolz and Schneuwly (2004), has also been reviewed. Data provide evidence that, despite some of the activities with the complaint letter text genre are still closely connected to the teaching of form and the genre structure, some activities elaborated by teachers show that teachers have used the PDG teaching device in a satisfactory way, althought, it requests improvement to the relevants language practices. The results lead to the importance of including more practice in the initial graduation of Portuguese teachers, as well as the need of constant investment in the continued graduation of the mother tongue teachers, so that they improve their interventions in the teaching overview of text genres, in which the processes of teaching-learning and the production of texts are included.